Analyzing the content of accounts of Algerian public main libraries on Facebook - Sayah, Fares; Djezairi, Samir (Journal of Social Sciences and Humanities, 2021)
Public libraries aim at providing quality information services to meet the needs of its customers from various fields by means of applying the latest methods in the field of information and network technology. Hence, social networks of all sorts have become one of the most important means available on the internet that help libraries to market their information services, and break through time and space obstacles. One of the most popular and user-friendly social networks is Facebook, which appeared in 2004 and is full of libraries accounts. Therefore, this study aims at analyzing the content of some accounts of Algerian public main libraries on Facebook Through the analysis of posts and interactions, thus identifying the most important services and topics offered by these libraries.